The number of parties and decision-making in legislatures - Marina Bannikova; Artyom Jelnov; Pavel Jelnov (Games, 2021)
This paper proposes a model of a legislature, formed by several parties, which has to vote for or against a certain bill in the presence of a lobbyist interested in a certain vote outcome. We show that the ease with which the lobbyist can manipulate a legislature decision increases with the number of elected parties, and, consequently, decreases with an electoral threshold. On the other hand, a lower electoral threshold increases the representativeness of a legislature. We combine these two effects in a notion of fairness. We show the existence of an electoral threshold that optimizes the fairness of a political system, which is close to 1-5%. Namely, the optimal threshold (in our sense) is close to thresholds that exist in most parliamentary democracies.
Keywords: 330; legislature; lobbyist; parties; voting